Corresponding influences of top-down control on task switching and long-term memory. Issue 6 (June 2015) - Richter, Franziska R.; Yeung, Nick
Three experiments investigated the impact of cognitive control on current performance and later memory in task switching. Participants first switched between object and word classification tasks, performed on picture–word stimuli that each appeared only once, then were tested for their recognition memory of these items. Each experiment replicated the recent finding that task switching results in reduced selectivity in later memory for task-relevant over task-irrelevant items. Top-down control was manipulated through varying the time available for advance task preparation (Experiment 1), the freedom of choice over which task to perform (Experiment 2), and the availability of reward incentives (Experiment 3). For each manipulation, more effective top-down control during task switching was associated with increased selectivity in memory for task-relevant information. These findings shed new light on the role of cognitive control in long-term memory encoding, in particular supporting an interactive model in which long-term memory reflects the enduring traces of perceptual and cognitive processes that operate under the selective influence of top-down control.